Análise de concentração de tensão do aço sae 1020 tratado termicamente - Barbosa, Larissa Moreira (Universidade Federal Rural do Semi-Árido, 2018)
Typically, mechanical components, such as machine elements, may have non-uniform cross-sections, such as: holes, tears, notches, among others. The presence of these discontinuities in the cross-sectional area in a structural component is necessary, in compliance with the engineering design. What makes a region critical, because it can present high values of localized stress in these regions, are called stress concentrators. In this way, the present work has the objective of analyzing the resistance of the material when it presents voltage concentrators The study was carried out using test specimens made from a thermally treated low carbon SAE 1020 low carbon bar, featuring stress concentrators, ½ inch diameter cross bores and their influence on the material. According to the results obtained from the stress versus strain curve obtained by conventional tensile tests, it was possible to perform the analysis of the concentrators in the material and to verify their influence on the heat treated material and without heat treatment. It was observed, according to statistical analysis, that there were variations in the properties evaluated with the presence of the stress concentrator, there being a tendency of the ductile material to behave in a fragile way when it presents a stress concentrator, as verified in the material flow. It was also possible to verify how the deformation of the treated and untreated material behaved, verifying an increase in deformation when the material was heat treated. In this way, we conclude that the material presented changes in the studied mechanical properties, as well as the importance of the study of stress concentrators as well as their influence on the material.
Monografia
Keywords: Resistência do material; Recozimento; Normalização; Ensaio de tração; ENGENHARIAS::ENGENHARIA MECANICA